If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P + -6 = 88 Reorder the terms: -6 + P = 88 Solving -6 + P = 88 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + P = 88 + 6 Combine like terms: -6 + 6 = 0 0 + P = 88 + 6 P = 88 + 6 Combine like terms: 88 + 6 = 94 P = 94 Simplifying P = 94
| (4x*10)/x | | 12x/48 | | -5+15x=13x+11 | | -3x+6(2x+11)=156 | | 5x-8=2x | | X-4/4=11 | | 5x=13+5x | | 1/2=14-x/6 | | 7m-4=2(5m-2)+6 | | 6x-6(-2x+4)=156 | | 2(x+5)+4(2x-1)=8x+12 | | 14x-10+6x-10=180 | | 10(h+1)-4=13 | | 3x/(3x-5)=(1/2) | | -4(t-3)=32 | | 0.3+0.2x=0.4+0.05 | | -3(x+5)=60 | | 3x+19=93 | | 62=2+2x | | -2+9x=-56 | | 3x/3x-5=1/2 | | 12/4x=60/109 | | 0,71/8 | | 4m-6=-46 | | 11x+32=108 | | 11x-32=108 | | 11x-32= | | 0,21/85 | | x/10=30/60 | | 0,130/48 | | 3y+36=7y | | 2.5-3ln(x+3)=5 |